Efficacy of Avène Hydrotherapy on Chronic Pruritus in Patients with Plaque Psoriasis - Marie-Dominique Thouvenin; Adeline Bacquey; Marine Babin; Fabrice Lestienne; Christophe Lauze; Eléonore Gravier; Diana Placintescu; Ariadna Ortiz-Brugués; Sonja Ständer (Adis, Springer Healthcare, 2023)
Abstract Introduction Pruritus is a prevalent symptom, described as one of the most bothersome of psoriasis. Specific itch management remains a challenge, for which hydrotherapy could be used as adjunct care to medical treatment. Therefore, we assessed the immediate and longer-term benefit of 3 weeks of Avène thermal spring water hydrotherapy on chronic pruritus in patients in addition to their usual psoriasis and/or pruritus management. Methods Twenty-six patients suffering from chronic pruritus due to psoriasis were evaluated before and after 3 weeks of hydrotherapy with a 3 and 6 month follow-up. A control group (18 patients) did not undergo hydrotherapy and continued to follow their usual skin management. Pruritus was assessed according to the numeric rating scale (NRS, pruritus intensity), the visual dynamic pruritus score (vDPS, change in pruritus intensity), and the 5-D itch scale (pruritus characteristics). Psoriasis severity was measured using the psoriasis area and severity index (PASI) score. The "itchy quality of life" (ItchQoL) scale was used to assess quality-of-life (QoL) impact related to itch. Pruritus and psoriasis gene and protein biomarkers were measured in lesional and nonlesional skin. Results Pruritus measurements (NRS, vDPS, and 5-D itch scale) indicated an immediate and long-lasting positive effect of hydrotherapy compared with control patients. The psoriasis area and severity index (PASI) was decreased by 40.0% by hydrotherapy, which was sustained over 6 months. The ItchQoL also improved directly after hydrotherapy, which was still much improved even 6 months later. Analysis of gene and/or protein biomarkers revealed a significant decrease of inflammation biomarkers (IL-8, IL-1α, IL-1RA, and RANTES), of psoriasis biomarkers (PI3, S100A7, and IL-17), and of pruritus biomarkers (IL-31, TRPV1, and CGRP1). Conclusions These findings demonstrated an immediate and long-lasting improvement of pruritus in patients with psoriasis who underwent Avène thermal spring water hydrotherapy, indicating that this would be a good complementary therapy in the management of this disease. Trial Registration NCT03023254.